SciPost Phys. Codebases 2022
DOI: 10.21468/scipostphyscodeb.7
|View full text |Cite
|
Sign up to set email alerts
|

NetKet 3: Machine Learning Toolbox for Many-Body Quantum Systems

Abstract: We introduce version 3 of NetKet, the machine learning toolbox for many-body quantum physics. NetKet is built around neural quantum states and provides efficient algorithms for their evaluation and optimization. This new version is built on top of JAX, a differentiable programming and accelerated linear algebra framework for the Python programming language. The most significant new feature is the possibility to define arbitrary neural network ansätze in pure Python code using the concise notation of machine-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Appendix A: Details of calculations All of our calculations were implemented in Netket 3.3 [68,75]. In one dimension, we found that a restricted Boltzmann machine works well, while in two dimensions, a group convolutional neural network functions better.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Appendix A: Details of calculations All of our calculations were implemented in Netket 3.3 [68,75]. In one dimension, we found that a restricted Boltzmann machine works well, while in two dimensions, a group convolutional neural network functions better.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, there still exists scalability issue as the parameter number continues to increase. One solution is to adopt approximate solutions, such as the sparse distributed solver as introduced in NetKet [41] and hybrid low-rank natural gradient method in [42]. Investigating the performance of these highly scalable sparse algorithms is one of our future directions.…”
Section: Distributed Sr Computationmentioning
confidence: 99%
“…Once we have the subset of approximate eigenstates in the form of an RBM, we use Metropolis sampling to estimate the matrix elements given in Equations ( 49) and (50). We used N σ = 5 × 10 6 samples for the estimate, resulting in a relative statistical error <10 −2 for the relevant matrix elements.…”
Section: Perturbation Theorymentioning
confidence: 99%